2020
DOI: 10.1038/s41419-020-02945-5
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MM2P-induced, exosome-mediated transfer of Sox9 from monocyte-derived cells modulates primary chondrocytes

Abstract: Monocyte-derived cells were shown to promote cartilage repair in osteoarthritis. The role of the long non-coding RNA (lncRNA) MM2P in this function of monocyte-derived cells remained unexplored. Treatment of RAW264.7 murine macrophages and mouse bone marrow-derived macrophages with IL-4 or IL-13 upregulated MM2P expression, upstream of STAT3 and STAT6 phosphorylation. Specifically, MM2P blocked SHP2-mediated dephosphorylation of STAT3 at Try705 and interacted with the RNA-binding protein FUS. In turn, p-STAT3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Numerous lncRNAs have been proved play critical roles in OA and mediate the apoptosis of chondrocytes [ 39 , 40 ]. Here, we first reported the downregulation of lncRNA HAND2-AS1 in OA, which can effectively distinguish OA patients from the healthy controls, suggest that downregulation of HAND2-AS1 may be used to assist the diagnosis of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous lncRNAs have been proved play critical roles in OA and mediate the apoptosis of chondrocytes [ 39 , 40 ]. Here, we first reported the downregulation of lncRNA HAND2-AS1 in OA, which can effectively distinguish OA patients from the healthy controls, suggest that downregulation of HAND2-AS1 may be used to assist the diagnosis of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several studies have been conducted about SHP2 in OA. For example, one study revealed that long non-coding RNA named MM2P can prevent SHP2-mediated dephosphorylation of STAT3, the activation of which promotes transcription of chondrocyte-specific protein Sox9 and contributes to cartilage repairment (Bai et al, 2020). Recently, Keisuke reported that the Ptpn11 gene is up-regulated in fibroblast-like synoviocytes of rheumatoid arthritis (RA) compared to that of OA (Maeshima et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The solution was kept heated for 15 min under stirring conditions until the colour became wine red, and the prepared AuNPs solution was then stored at 4 ℃ and protected from light. Transmission electron microscope (TEM) was used to examine the prepared gold nanoparticles (25,26). A concentration gradient for HLA-G was prepared using a standard solution (10, 20, 50, 100, 200, 500, and 1,000 nmol/L) and stored at 4 ℃ for later use.…”
Section: Detection Of Hla-g Based On Aunps-aptamer Sensing Methodsmentioning
confidence: 99%